Model-based prediction of spatial gene expression via generative linear mapping - Yasushi Okochi (Nature Portfolio, 2021)
Single cell RNA-seq loses spatial information of gene expression in multicellular systems because tissue must be dissociated. Here, the authors show the spatial gene expression profiles can be both accurately and robustly reconstructed by a new computational method using a generative linear mapping, Perler.